The Relationship Of Professionalism Competency To Student's Learning Motivation In Pubjects PAI : SMK Syahida - Ina Maryana; Deden Syarif Hidayatulloh (ASWAJA: Jurnal Pendidikan dan Keislaman, 2022)
This research is motivated by the role of a teacher, which is so crucial that it becomes a milestone in learning success in schools to achieve educational goals. A teacher is also a role model to foster students' motivation to learn so that learning goes well. This study aimed to determine the relationship between professional competence and student learning motivation in PAI at SMK Syahida, where the sample in this study amounted to 40 people using random techniques. The results of this study showed that The interpretation of teacher competence (variable X) is indicated by an average number of 4.45. The number 4.45 is included in the good category because it is in the interval 3.50 – 4.50. The interpretation of learning motivation (variable Y) is indicated by the average number of 3.69. The number 3.69 is included in the good category because it is in the interval 3.50 – 4.50. Then the reality of the relationship between professional competence and student learning motivation in PAI at SMK Syahida at a value of 0.18 in an interval of 0.00 – 0.19. The level of influence of variable X on variable Y is 2%, while other factors influence 98%.